The Influence of Employer Attractiveness and Corporate Reputation on Generation Z’s Job Application Interest in Startup Companies - Rizqullah, Ayun Anindita; Pramono, Tangguh Dwi; Pratami, Eggi Indriani (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2026)
In this digital era, start-up companies continue to grow, with the number reaching 2,637 companies in Indonesia by 2024. Generation Z, which is known to be technologically literate or tech-savvy, is considered to be very suitable for the characteristics of startups related to technology such as websites and the internet. However, recently many startups have gone bankrupt and had to close, resulting in mass layoffs. This damages the reputation of startups in the eyes of customers, investors and job seekers, especially Generation Z. This research aims to find out whether Generation Z is still interested in applying for jobs at startups based on employer attractiveness and corporate reputation. The research was conducted on final year students in Greater Bandung using a quantitative explanatory method, using a questionnaire distributed to 214 respondents via Google Forms. The data was processed using the IBM SPSS 26 application. The research results showed that there was a positive and significant influence of employer attractiveness and company reputation on Generation Z's interest in applying for jobs, especially final year students in Greater Bandung